2017
DOI: 10.1007/s10974-017-9487-3
|View full text |Cite
|
Sign up to set email alerts
|

When signalling goes wrong: pathogenic variants in structural and signalling proteins causing cardiomyopathies

Abstract: Cardiomyopathies are a diverse group of cardiac disorders with distinct phenotypes, depending on the proteins and pathways affected. A substantial proportion of cardiomyopathies are inherited and those will be the focus of this review article. With the wide application of high-throughput sequencing in the practice of clinical genetics, the roles of novel genes in cardiomyopathies are recognised. Here, we focus on a subgroup of cardiomyopathy genes [TTN, FHL1, CSRP3, FLNC and PLN, coding for Titin, Four and a H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 203 publications
(241 reference statements)
0
10
0
Order By: Relevance
“…FHL1 localizes to the sarcomere and the sarcolemma and is believed to participate in muscle growth and differentiation, as well as in sarcomere assembly. Recent studies have indicated that mutations in four and-a-half LIM domain protein 1 (FHL1) are associated with rare hereditary myopathies, including reducing body myopathy (RBM), X-Linked myopathy with postural muscle atrophy (XMPMA), Emery-Dreifuss muscular dystrophy (EDMD), and cardiomyopathies ( Kley et al, 2016 ; Xue et al, 2016 ; Ehsan et al, 2017 ; Pillar et al, 2017 ; Le Thanh et al, 2017 ). All these hereditary myopathies exhibit clinical features of muscular dysfunction including progressive muscular weakness, postural muscle atrophy and muscle wasting and weakness ( Schessl et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…FHL1 localizes to the sarcomere and the sarcolemma and is believed to participate in muscle growth and differentiation, as well as in sarcomere assembly. Recent studies have indicated that mutations in four and-a-half LIM domain protein 1 (FHL1) are associated with rare hereditary myopathies, including reducing body myopathy (RBM), X-Linked myopathy with postural muscle atrophy (XMPMA), Emery-Dreifuss muscular dystrophy (EDMD), and cardiomyopathies ( Kley et al, 2016 ; Xue et al, 2016 ; Ehsan et al, 2017 ; Pillar et al, 2017 ; Le Thanh et al, 2017 ). All these hereditary myopathies exhibit clinical features of muscular dysfunction including progressive muscular weakness, postural muscle atrophy and muscle wasting and weakness ( Schessl et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…CSRP3 (Muscle LIM Protein) MLP KO cardiomyocytes exhibit cytoarchitectural perturbations including disrupted myofibrillar assembly, abnormal alignment of Z-disks and marked fibrosis. In contrast, for some (but not all) HCM/RCM patients with Filamin C pathogenic variants, protein aggregation has been observed in vivo and in vitro 3 .…”
Section: Pathological Differential Diagnosis Of Hcmmentioning
confidence: 93%
“…Hypertrophic cardiomyopathy is most frequently a disease of the sarcomeric proteins. Mutations in several genes encoding thin and thick filament and the Z disk proteins of the sarcomeres ( MYH7, TPM1, TNNT2, MYBPC3, FHL1, CSRP3, FLNC, PLN) have been described 3 . The histopathological appearance varies according to the genetic defect, with the most severe morphological abnormalities being present in pediatric and early onset cases 4 .…”
Section: Pathological Differential Diagnosis Of Hcmmentioning
confidence: 99%
“…Titin is supposed to "…sense the mechanical stimuli and transform them into biochemical signals…" [34]. Great attention is now focused on the study of titin role in cardiomyopathies and skeletal muscle diseases [2,[39][40][41][42][43][44][45][46][47].…”
Section: Electrophoresis -Life Sciences Practical Applications 46mentioning
confidence: 99%